Night census and infrared technology monitoring of a black rhinoceros' population and species competition monitoring to inform management action in Tsavo, Kenya - Sospeter M Kiambi; Kenneth Murithi; Grace Waiguchu; Kenneth Ochieng; Cedric Khayale; Linus Kariuki; Patrick Omondi (Pachyderm)
We present the results of the 2019 night census of the black rhino (Diceros bicornis) population in Tsavo West National Park, Kenya. A dedicated rhino sanctuary was established in 1986 as part of efforts by the Kenyan government to safeguard the remaining populations of the critically endangered black rhino, and now contains more than 13% of the national population. In response to the challenges involved in observing black rhinos in their natural habitat, population numbers in the sanctuary are monitored using night censuses based on observation of rhino visits to artificial water holes. The 2019 night census recorded 96.2% of the known rhinos in the sanctuary, confirming that this is reliable method for monitoring rhino populations, with potential for use in other areas. It also provides information on health and population structure that are not obtainable by other methods. The results indicate that numbers of black rhino in the sanctuary continue to increase, albeit at a slower rate than in previous years. This slowdown likely reflects intraspecific competition for food resources as population density now stands at more than double the recommended ecological carrying capacity (EEC). The survey also found evidence of interspecific competition with other browsers, as well as a threat from predation of young animals by hyenas. We recommend further study of all these aspects, as well as continued translocation of surplus rhinos from the sanctuary to repopulate surrounding areas.